Comparison of global inventories of CO2 emissions from biomass burning during 2002–2011 derived from multiple satellite products. (November 2015) - Shi, Yusheng; Matsunaga, Tsuneo; Saito, Makoto; Yamaguchi, Yasushi; Chen, Xuehong
Abstract: This study compared five widely used globally gridded biomass burning emissions inventories for the 2002–2011 period (Global Fire Emissions Database 3 (GFED3), Global Fire Emissions Database 4 (GFED4), Global Fire Assimilation System 1.0 (GFAS1.0), Fire INventory from NCAR 1.0 (FINN1.0) and Global Inventory for Chemistry-Climate studies-GFED4 (G-G)). Average annual CO2 emissions range from 6521.3 to 9661.5 Tg year −1 for five inventories, with extensive amounts in Africa, South America and Southeast Asia. Coefficient of Variation for Southern America, Northern and Southern Africa are 30%, 39% and 48%. Globally, the majority of CO2 emissions are released from savanna burnings, followed by forest and cropland burnings. The largest differences among the five inventories are mainly attributable to the overestimation of CO2 emissions by FINN1.0 in Southeast Asia savanna and cropland burning, and underestimation in Southern Africa savanna and Amazon forest burning. The overestimation in Africa by G-G also contributes to the differences. Highlights: Five widely used global biomass burning emissions inventories were compared. Global CO2 emissions compared well while regional differences are large. The largest differences were found in Southeast Asia and Southern Africa. Savanna burning emission was the largest contributor to the global emissions. Variations in savanna burning emission led to the differences among inventories. Abstract : Differences of the five biomass burning CO2 emissions inventories were found in Southeast Asia and Southern Africa due to the variations in savanna burning emissions estimation.